2008
DOI: 10.1258/ijsa.2007.007160
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Chlamydia trachomatis and associated risk factors in women inmates admitted to a youth offenders institute in the UK

Abstract: The aim of the study was to estimate the prevalence of Chlamydia trachomatis genital infections in young women inmates aged 17-21 located on the Youth Offenders Institute of HMP Holloway. The study consisted of a questionnaire and a urine sample for analysis. A health advisor administered a questionnaire to establish sociodemographic profile, sexual history and illicit drug use. C. trachomatis was diagnosed using a nucleic acid amplification test. Overall, the prevalence of C. trachomatis was 13.2%. Drug use w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
7
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
1
7
0
2
Order By: Relevance
“…Sir: At the risk of suggesting yet another entry to the list of horrors -e.g. HIV, malaria, tuberculosis, poverty, drought, food shortages -bedevilling a region that, at this point, deserves only relief, it should be noted that the paper by Chersich et al 1 in the November issue of International Journal of STD and AIDS generally substantiates the conclusions of a recent spate of papers 2 -8 that have called attention to the role of hazardous drinking in sub-Saharan HIV/AIDS spread. This is an issue that received far too little attention from the local and international HIV prevention and policy-making community during earlier years of the pandemic.…”
mentioning
confidence: 74%
“…Sir: At the risk of suggesting yet another entry to the list of horrors -e.g. HIV, malaria, tuberculosis, poverty, drought, food shortages -bedevilling a region that, at this point, deserves only relief, it should be noted that the paper by Chersich et al 1 in the November issue of International Journal of STD and AIDS generally substantiates the conclusions of a recent spate of papers 2 -8 that have called attention to the role of hazardous drinking in sub-Saharan HIV/AIDS spread. This is an issue that received far too little attention from the local and international HIV prevention and policy-making community during earlier years of the pandemic.…”
mentioning
confidence: 74%
“…Chlamydia and gonorrhoea share some risk factors, such as female gender, younger age at sexual debut, low contraceptive use, greater number of sexual partners, engaging in commercial sex work and drug use. 712 Recent studies have also identified partner-level risk factors; for example, in a sample of 15–24 year olds, partners who had a sexually transmitted infection (STI) in the past year and partnerships with an age difference of five years or more were more predictive of STIs than were the individuals' own sexual behaviours. 13 STI risks may also differ by sexual partner type.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a study of young prisoners in the United Kingdom revealed a chlamydia prevalence of 13.2%, compared with 5% in the UK general community (Adams, Charlett, Edmunds, & Hughes, 2004;Gabriel, Burns, Scott-Ram, Adlington, & Bansi, 2008). In California, United States chlamydia prevalence among men and women prisoners aged 18Á25 years averaged 9.4%, compared with a prevalence of 2.2% among males and females aged 14Á39 years in the general community (Bernstein et al, 2006;Datta et al, 2007).…”
Section: Introductionmentioning
confidence: 99%